Estrutura, Impacto e Significado da Dívida Pública Moçambicana com os BRICS (2006-2015) - Fernanda Massarongo; Sérgio Chichava (Cadernos de Estudos Africanos)
Between 1990s and 2000s, Mozambique experienced a significant reduction in its external public debt owing to different debt relief initiatives. As a result, debt dropped from 150% of the GDP to about 50% of the GDP. However, from this point, public debt spiked, re-approaching 100% of the GDP. An important driver of this growth was the debt contracted with the group of countries known by the acronym BRICS. Between 2008 and 2014, Mozambique debt to the BRICS rose by more than nine times from around US$ 191 million to about US$ 1.8 billion. In line with this, this article seeks to understand the characteristics of the Mozambique’s debt to the BRICS between 2006 and 2015.